Proactive criminal thinking and the transmission of differential association: a cross-lagged multi-wave path analysis - Walters, Glenn D. (Criminal justice and behavior, 2015)
The purpose of this study was to determine whether proactive criminal thinking mediated the relationship between peer delinquency and future serious offending better than peer delinquency mediated the relationship between proactive criminal thinking and future serious offending. Participants in this study were 1,027 ten- to eighteen-year-old British youth (458 boys, 569 girls) from the four-wave Offending, Crime and Justice Survey (OCJS). Prior delinquency was controlled by confining the sample to individuals who denied pre-existing delinquency involvement. In line with the main hypothesis, the peer delinquency ? proactive criminal thinking ? serious offending path achieved a significantly stronger effect than the proactive criminal thinking ? peer delinquency ? serious offending path. These findings provide support for a synthesis of social learning and criminal thinking theories in which peer delinquency helps shape proactive criminal thinking, and proactive criminal thinking effectively mediates the relationship between peer delinquency and serious offending.